INTERPERSONAL CONFLICT BETWEEN STUDENTS IN SCHOOL: HOW DO THE PRINCIPALS RESOLVE IT? - Moh. Badruddin Amin (re-JIEM (Research Journal of Islamic Education Management), 2021)
The principal is a person who determines the central point of a school institution which has a complex role, including in resolving conflicts. Conflict is a conflict in human relations between one party and another that arises from differences that result in positive and negative things.